Hand hygiene knowledge, attitudes, and self-reported practices among medical and nursing staff of a tertiary-care military hospital: a cross-sectional study - Zia, Iqra; Cheema, Sidra Shafiq; Sheikh, Naveen Siddique; Ashraf, Huma (International Journal of Infection Control, 2022)
Hand hygiene (HH) serves as a primary public health measure against healthcare-associated infections. During the coronavirus disease 2019 (COVID-19) pandemic, caused by the severe acute respiratory syndrome (SARS) coronavirus 2 (SARS-CoV-2), HH has been fundamentally reinforced for preventing infection transmission globally. This cross-sectional study provides data as a baseline evaluation of knowledge, attitude, and self-reported practice, along with the differences of each between medical and nursing staff. A self-administered questionnaire comprising a standardized World Health Organization Hand Hygiene Knowledge Questionnaire (WHO, revised August 2009) and Likert scales for attitude and practice was employed, using convenience sampling to collect data from 383 healthcare workers (HCWs), 92 nurses (24.9%), and 277 doctors (75.1%) in a tertiary-care military hospital. Both nurses and doctors had moderate knowledge with no significant difference (P = 0.54). Moreover, attitude and practice were reported as moderate for both groups. However, the self-reported HH practice of doctors was significantly (P < 0.05) better than that of nurses, while nurses had significantly better (P < 0.01) attitudes in comparison with doctors. Participants who had received formal training in the previous 3 years were 70.65% among nurses and 44.76% among doctors. In total, 78.36% acknowledged routine use of alcohol-based hand rub. It suggested a relationship of HH to demographic variables, professional role, and departmental service. It should be noted that this study shows no relationship between knowledge and practice, and a negative correlation between knowledge and attitude. Concurrently, while further investigation is required to pinpoint the obstacles to achieving proper HH, it can be concluded that infrastructure promoting its practice among HCWs needs to be established.